Framing Sustainable Mobility : How to Ensure that Today's Mobility Needs Are Not Met at the Expense of Future Generations - Vandycke, Nancy; Kauppila, Jari (World Bank, Washington, DC, 2018)
In its crucial role, transport fosters development as it connects people to goods, services, social, and economic opportunities. But today’s data shows social exclusion linked to accessibility gaps in transport services—in rural areas, women, and the elderly—, high costs tosociety from poorly integrated transport systems, road fatalities, traffic congestion, air pollution, and environmental degradation. The question for global and country transportdecision-makers is how to meet the mobility needs of people and goods now, while preserving futuregenerations? The 2030 Agenda for Sustainable Development and the Sustainable Development Goals (SDGs) identify an important and rich array of characteristics that define a sustainable world. Those characteristics, along with those identified in the economic literature, can be used to frame“sustainable mobility” around four global goals, which should address more than access. Formobility to be sustainable, it should have four attributes—equitable, efficient, safe, and green. In this way, mobility can benefit both present and future generations.